The Breastfeeding with Nutritional Status Based on Toddler’s Height in Bondowoso - Candrika Eka Prabawati; Syaiful Bachri; Jamhariyah J (D'Nursing and Health Journal (DNHJ), 2022)
Introduction: The incidence of stunting in toddler in Indonesia has been above the WHO target. In Bondowoso, the prevalence of stunting in February 2019 reached 17.54% of 45,002 toddlers. Stunting is closely related to inadequate nutrition, one of which is exclusive breastfeeding. The purpose of research was to determine the relationship of breastfeeding with nutritional status based on toddler’s height in Walidono Village, Prajekan District, Bondowoso Regency. Methode: The type of research was a correlational study with a case control approach. Total population of 46 toddlers aged 24-36 months and obtained a sample of 41 toddlers with proportional random sampling technique. The instrument used questionnaires giving ASI, microtoise and z score application. Data analysis used Chi Square test and obtained the Contingency Coefficient value with the help of the SPSS 26. Results: The results shows 51.22% of toddlers with no history of exclusive breastfeeding and 48.78% were given exclusive breastfeeding, toddler stunting 43.90% and not stunting 56.10%. The analysis results obtain  p-value of 0.039 <α (0.05), it can be concluded that H0 is rejected Ha is accepted, with a Contingency Coefficient value of 0.306 meaning that there is a relationship between breastfeeding and nutritional status based on toddler’s height in Walidono Village, Prajekan District, Bondowoso Regency. Conclusion: Midwives are expected will increase the provision of information on exclusive breastfeeding to pregnant and breastfeeding mother in order to prevent stunting in toddler.